The Substitutability of Natives and Immigrants in Production - Grossman, Jean Baldwin (The Review of Economics and Statistics, 1982)
T HE United States is a country of immigrants and sons and daughters of former immigrants. From colonial times to the 1920s, America had an open door immigration policy. Although the formal policy generally welcomed immigrants, those who preceded the newcomers have never looked kindly on the arrival of new immigrants. Xenophobia has been a common reaction by Americans to large scale inflows. Although ethnocentrism undoubtedly is one reason for such isolationist feelings, fear of economic displacement is another underlying cause.' At the center of the debates over immigration policy has been the fear that the newcomers take jobs away from native Americans. The substitutability of natives for immigrants is critical in evaluating the validity of the displacement fears. A number of theoretical contributions, including Gerking and Mutti (1979), Grossman (1981) and Johnson (1980a) have dealt with the economic effects of international labor inflows. However, no empirical investigation of these issues has been undertaken. The absence of such studies is due, at least in part, to the lack of accurate data on the number of employed illegal immigrants, who comprise a substantial portion of the immigrant stock. While it is currently not possible to develop empirical estimates of the substitutability of illegal immigrants and natives, or even between the most recent wave of legal immigrants and natives, it is nonetheless useful to investigate the relationship in production that has historically existed between immigrants and the domestic labor force. In what follows, I use cross-section data for 1970, the most recent year for which such data are available, to estimate aggregate production relationships. The resulting estimates shed light on the substitutability between the stock of immigrants in the United States at that time, and the native work force. Until more is known about the employment behavior of more recent illegal and legal (especially refugee) immigrants, this is the best that can be accomplished.